NATIONAL STRATEGIC PLAN AND CUSTOMARY LAW FOR LAND DISPUTE REGULATIONS - Farhan, Mohammad (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
One of the causes of agricultural conflicts that still occur frequently today is customary land. Understanding the background of land customary law is essential to building a treatment model and identifying the underlying issues causing the dispute. This study uses normative jurisprudence research methods; in particular, legal studies that view law as the basis of a normative system are typical. The authority vested in the Minister of Agriculture and Spatial Planning/Director of the Land Agency to recommend spatial adjustments to the location of the National Strategic Project to propose a solution at this time further strengthens the possibility of legally binding changes to the spatial plan. In particular, the study of law, which views law as the structure of a normative system. Conflicts usually arise because governments, the private sector, or the communities have different land-use goals. These customary land disputes often contradict Law No. 5 of 1960 on the basic regulations of the community's cultural norms and agricultural principles. Litigation and non-litigation are two possible approaches to dispute resolution. Conflicts usually arise because governments, the private sector, or the communities have different land-use goals. These customary land disputes often contradict Law No. 5 of 1960 on the basic regulations of the community's cultural norms and agricultural principles. The action to be taken when resolving a dispute can be in the form of litigation and non-litigation.